2020
DOI: 10.21203/rs.3.rs-40063/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exogenous coronavirus interacts with endogenous retrotransposon in human cells

Abstract: Abstract Background: There is an increased global outbreak of diseases caused by coronaviruses affecting respiratory tracts of birds and mammals. Recent particularly dangerous coronaviruses are MERS-CoV, SARS-CoV and SARS-CoV-2, causing respiratory illness and even failure of several organs. However, profound impact of coronavirus on host cells remains elusive. Results: Here, we go deep into transcriptome of MERS-CoV, SARS-C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 50 publications
5
26
0
Order By: Relevance
“…We next quantified the reads that partly mapped to the human genome and partly mapped to the SARS-CoV2 genome (see methods ). We found that nearly 0.05-1% of all viral reads are formed of hybrid sequences between host and virus RNAs, a frequency consistent with that recently reported by others 15,16 ( Fig. 1C ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We next quantified the reads that partly mapped to the human genome and partly mapped to the SARS-CoV2 genome (see methods ). We found that nearly 0.05-1% of all viral reads are formed of hybrid sequences between host and virus RNAs, a frequency consistent with that recently reported by others 15,16 ( Fig. 1C ).…”
Section: Resultssupporting
confidence: 92%
“…RNA-sequencing reads that partly align to the host genome and partly align to the viral genome are the signature of HVC events in RNA-sequencing datasets. Recent reports 15,16 suggesting the presence of HVC events in SARS-CoV2-infected cells have been interpreted as supporting viral integration into the human genome as a mechanism of viral persistence. To gain insights into the authenticity of these events, we re-analyzed the 3 available RNA-seq datasets from patients with COVID-19 (n=57 samples) and in vitro SARS-CoV2 infected cells (n=64 samples).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Dr. Bing Li from Shanghai Jiao Tong University for assistance of data analysis on retrotransposon expression. This manuscript has been released as a pre-print at ResearchSquare ( Yin Y et al., 2020 ).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Recent studies reported a high frequency of reverse transcription and integration of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in infected cells (Zhang et al, 2020;Ying et al, 2021), with implications for diagnostic detection of SARS-CoV-2 nucleic acids by RT-qPCR and for viral antigen persistence. These findings were partly based on the identification of chimeric reads between viral and human RNA in next-generation RNA-sequencing (RNA-seq) data (Zhang et al, 2020;Ying et al, 2021). Here, we examined the potential source of such chimeric reads and found that they are more likely to be a methodological product, than the result of genuine reverse transcription, integration and expression.…”
Section: Introductionmentioning
confidence: 99%